Spatial variability of soil chemical attributes in arabica coffee (Coffea arabica L.) fields under different management systems - Fagioli da Silva, Alessandra; Soares de Souza Lima, Julião; Soares de Souza, Gustavo; Batista de Oliveira, Rone (Coffee Science - ISSN 1984-3909)
The objective of this work was to assess the spatial variability of the chemical attributes of two coffee areas, managed in conventional and organic crop systems, and to calculate the percent of variation between them. In each area, a 40-point-mesh was sampled at 0-0.10 m and 0.10-0.20 m layers, within the crown projection, for pH, SB, K, P, Ca and Mg analysis. The data were analyzed through descriptive statistics and geostatistics. From the soil chemical attributes map, the percent of variation between the systems’ chemical attributes was determined by GIS algebraic operations. The results show that the soil chemical attributes present a spatial dependence in both systems and layers. Analysis of the soil chemical attributes showed less spatial variability in the organic system, in relation to the conventional, indicating homogeneous zones for different fertilizer applications. The percent of variation of the chemical attributes in the conventional system, in relation to the organic, at 0-0.10 m and 0.10-0.20m layers are 54.80% and 35.61%, respectively.